The effects of Papaver somniferum (Opium poppy) on health, its controversies and consensus evidence. (3rd July 2022) - Hedayati-Moghadam, Mahdiyeh; Moezi, Seyyed Ali; Kazemi, Toba; Sami, Abdul; Akram, Muhammad; Zainab, Rida; Khazdair, Mohammad Reza
Abstract: After cannabis, opiates are the world's second most widely abused illegal drug. Opium is the latex of unripe pods of Papaver somniferum (Opium poppy). Opium has been used traditionally for lowering blood lipids, and postpone cardiac diseases, as well as used for the treatment of diabetes and cancer. In eastern countries, the high prevalence of opium use could be attributed to high supply and conventional assumptions. Although, opium consumption reduced the levels of lipid profile and fasting blood sugar (FBS) in patients, while it also reduced left ventricle ejection fraction. Opium consumption increased inflammatory lung disease and risk of lung cancer as well as increased free radicals by activating lipid peroxidation.